Cloning of linear T-cell epitops of EG95 antigen of Echinococcus granulosus into pGEX4t1 vector and expression analysis by SDS-PAGE - Roghayeh Mesri; Majid Esmaelizad; Mmozhghan Ahmadzadeh; Somayeh Mohammadi; Seyed Abdolhamid Angaji; Zahra Yazdanpour; Seyedeh Fahimeh Mmir Haghghouy Jali (Fasa University of Medical Sciences, 2016)
Background & Objectives: Echinococcus granulosus causes a common disease between humans and animals that called hydatid cyst or hydatidosis. The recombinant EG95 vaccine based on cloning of the 25 KD oncospheral antigen-Eg95- in pGEX stimulated significant humoral and cellular immunity in sheep, but regarding the effect of TH1cell immunity against this parasite and the influence of the linear T-cell epitopes in stimulating this immunity, only the coding sequence of linear T Cell epitopes of EG95 was cloned in pGEX and analyzed it's expression to optimize the qualification of this available vaccine in this study. Materials & Methods: The coding sequence of EG95 linear epitopes by IEDB software were predicted and synthesized. After PCR, the amplicon and pGEX4T1 were digested by xhoI restriction enzyme, the fragment was cloned into pGEX4T1 by heat shock method, and Positive colonies were selected by direct PCR with specific primers. The recombinant protein expression was evaluated in BL21 cells by 10% SDS-PAGE. Results: The coding sequence of EG95 linear T-cell epitopes was amplified by PCR and cloned into pGEX4T1 vector.  The recombinant plasmid was selected with Colony PCR and size difference between intact and recombinant purificated vectors. Recombinant protein expression with high significant concentration was recognized by SDS-PAGE. Conclusion: The EG95 linear T-cell epitopes coding sequence has been successfully cloned into pGEX4T1 vector and expressed into BL21 cells.